Precipitation hardened powder metal composition

JP7943909B2Active Publication Date: 2026-10-30GKN SINTER METALS LLC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024533006
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-03
Filing Date
2022-07-29
Publication Date
2026-10-30
Estimated Expiration
2042-07-29

AI Technical Summary

Benefits of technology

【0019】 本発明のこれらの利点及び他の利点は、詳細な説明及び図面から明らかである。以下は、本発明の幾つかの好ましい実施形態の説明にすぎない。本発明の全範囲を評価するには、特許請求の範囲を参照する必要があり、これはなぜならば、これらの好ましい実施形態は、特許請求の範囲内の唯一の実施形態であることを意図したものではないからである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007943909000011
    Figure 0007943909000011
  • Figure 0007943909000012
    Figure 0007943909000012
  • Figure 0007943909000013
    Figure 0007943909000013
Patent Text Reader

Abstract

The powder metal compositions are compacted, sintered, and heat treated to provide a powder metal material comparable to wrought 6013 aluminum alloy. The powder metal compositions include aluminum based powder metal, aluminum-silicon powder metal, aluminum-copper powder metal, and elemental magnesium powder metal. The weight percentage of silicon in the powder metal composition is within the range of 0.6-1.0 weight percent of the powder metal composition, the weight percentage of copper in the powder metal composition is within the range of 0.7-1.1 weight percent of the powder metal composition, and the weight percentage of magnesium in the powder metal composition is within the range of 0.8-1.2 weight percent of the powder metal composition. The powder metals can be compacted to form a green compact and further sintered and heat treated to provide a powder metal composition comparable to wrought 6013 aluminum alloy.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] Cross-references to related applications This application claims the benefit as of the filing date of U.S. Provisional Patent Application No. 63 / 285,804, entitled “Precipitation-Hardening Powder Metal Composition,” filed on 3 December 2021, and the benefit as of the filing date of U.S. Provisional Patent Application No. 63 / 285,871, entitled “Hot Deformation Treatment of Precipitation-Hardening Powder Metal Alloy,” both of which are incorporated herein by reference for any purpose as if they were described herein in their entirety.

[0002] Statement on federally sponsored research or development Not applicable.

[0003] This disclosure relates to powder metallurgy formulations and sintered parts manufactured therefrom. In particular, this disclosure relates to powder metal compositions that serve as substitutes for forged 6013 aluminum alloys. [Background technology]

[0004] 6013 aluminum alloy is a precipitation-hardening aluminum alloy containing magnesium (Mg) and silicon (Si) as its main alloying elements. It possesses excellent mechanical properties and weldability, as well as superior corrosion resistance. This combination of properties makes it one of the most widely used aluminum alloys. Aluminum 6013 is used in a wide range of applications, including aerospace components, automotive components, valve components, machine components, military equipment, brake systems, and hydraulic applications. In this specification, the composition of 6013 aluminum alloy should be understood to mean, by weight percent, 94.8% to 97.8% aluminum, 0.8% to 1.2% magnesium, 0.60% to 1.0% silicon, 0.60% to 1.1% copper, 0.20% to 0.80% manganese, 0.50% or less iron, 0.25% or less zinc, 0.10% or less chromium, and 0.10% or less titanium, with the remaining elements each at 0.050% or less, totaling 0.15% or less.

[0005] In 6013 alloys, magnesium and silicon form the basis of the heat treatment of this system, creating the Mg2Si intermetallic phase that improves mechanical properties. Copper also contributes to the improvement of mechanical properties. Iron is present as an impurity and forms various intermetallic phases that affect corrosion and mechanical properties.

[0006] While there are many methods for forming metal parts, powder metallurgy (PM) processes represent a class of manufacturing techniques for forming metal parts. In powder metallurgy, powder metal material is typically manufactured or obtained, and this powder metal material is compressed in a set of tools and molds to form a green compact or preform that closely resembles the desired final product shape. The green compact is then sintered so that the powder metal particles diffuse with each other, densifying into a more mechanically strong object. Powder metallurgy is suitable for mass production of parts and has the advantages of low scrap costs and the ability to produce parts that do not require machining after forming.

[0007] This is merely a general overview of powder metal manufacturing processes, but what can be seen from this description is that many powder metal processes are typically carried out in a solid state or with a limited amount of liquid formed during the sintering process. However, this also highlights some challenges when using powder metal processes, because sintering is a diffusion-dependent process, and the resulting microstructure and porosity are functions of the powder composition and processing conditions. Thus, when attempting to convert forged or cast alloys into powder metal formulations, the challenge arises of creating a comparable microstructure and providing comparable mechanical properties. [Overview of the Initiative]

[0008] Currently, there is no powder metal equivalent to cast "forged" 6013 aluminum alloy. From the background technology section above, it is clear that many forged alloys cannot be manufactured simply by combining various elemental powders, as powder metal processes are diffusion-dependent and the resulting form may not be comparable to, for example, cast parts with a similar chemical composition in other respects. Furthermore, because powder metal parts are sintered with various particles together, they usually have some degree of porosity after conventional sintering processes, and this porosity can negatively affect the material properties compared to perfectly dense parts.

[0009] This specification discloses a powder metal composition comparable to a forged 6013 aluminum alloy. This powder metal 6013 aluminum alloy adds another potential alloy to the toolbox of materials available for new applications and could open the door to the production of parts from powder metals, which has previously been limited to the production of forged alloys. Such alloys would be particularly useful in the production of electric vehicle parts. Furthermore, metal matrix composite (MMC) additives can be added to the 6013 powder metal composition and the parts made therefrom to improve wear resistance and strength.

[0010] According to one embodiment, the powder metal composition provides a powder metal material comparable to a forged 6013 aluminum alloy when compressed, sintered, and heat-treated. The powder metal composition includes aluminum-based powder metal (defined here as powder metal containing pure aluminum without effective alloying elements, or powder metal in which alloying elements are 2% by weight or less of the aluminum-based powder metal), aluminum-silicon powder metal, aluminum-copper powder metal, and elemental magnesium powder metal. The weight percentage of silicon in the powder metal composition is in the range of 0.6 to 1.0% by weight of the powder metal composition, the weight percentage of copper in the powder metal composition is in the range of 0.7 to 1.1% by weight of the powder metal composition, and the weight percentage of magnesium in the powder metal composition is in the range of 0.8 to 1.2% by weight of the powder metal composition.

[0011] In some forms, the aluminum-based powder metal may be pure aluminum without any effective alloying elements pre-alloyed to the aluminum-based powder metal. In this form, the powder metal composition further contains elemental tin powder metal, and the weight percentage of tin in the powder metal composition may be in the range of 0.2% to 1.0% by weight of the powder metal composition. In some forms, the weight percentage of silicon in the powder metal composition is narrower, in the range of 0.7 to 0.9% by weight of the powder metal composition, the weight percentage of copper in the powder metal composition is narrower, in the range of 0.8 to 1.0% by weight of the powder metal composition, the weight percentage of magnesium in the powder metal composition is narrower, in the range of 0.9 to 1.1% by weight of the powder metal composition, and the weight percentage of tin in the powder metal composition is narrower, in the range of 0.4 to 0.6% by weight of the powder metal composition, and the remainder of the powder metal composition is assumed to be aluminum with only trace amounts of other ineffective alloying elements added. More specifically, in a particular form, the weight percentage of silicon in the powder metal composition may be 0.8% by weight of the powder metal composition, the weight percentage of copper in the powder metal composition may be 0.9% by weight of the powder metal composition, the weight percentage of magnesium in the powder metal composition may be 1.0% by weight of the powder metal composition, and the weight percentage of tin in the powder metal composition may be 0.5% by weight of the powder metal composition.

[0012] In some embodiments, the aluminum-based powder metal may be aluminum powder metal pre-alloyed with manganese such that the weight percentage of manganese in the powder metal composition is in the range of 0.2 to 1.2 wt% of the powder metal composition. In this embodiment, the weight percentage of manganese in the powder metal composition may be more narrowly in the range of 0.4 to 0.6 wt% of the powder metal composition. More specifically, in one particular embodiment, in the powder metal composition, the weight percentage of manganese in the powder metal composition may be 0.5 wt% of the powder metal composition. If the aluminum-based powder metal is pre-alloyed aluminum powder metal alloyed with manganese, the powder metal composition further contains elemental tin powder, and the weight percentage of tin in the powder metal composition may be in the range of 0.2 to 1.0 wt% of the powder metal composition, and may aim for about 0.5 wt%.

[0013] In various forms, aluminum-based powder metals, and whether they are pure or pre-alloyed, can further contain elemental tin powder, and the weight percentage of tin in the powder metal composition is in the range of 0.2 to 1.0 wt% of the powder metal composition, with a target of about 0.5 wt%.

[0014] In some forms, aluminum-silicon powder metal may be Al-12Si master alloy powder metal (approximately 88 wt% aluminum and 12 wt% silicon), and aluminum-copper powder metal may be Al-50Cu master alloy powder metal (approximately 50 wt% aluminum and 50 wt% copper).

[0015] In some forms, the powder metal composition further contains a lubricant, and the weight of the lubricant is not included in the weight percentage of the alloying elements. This may be the case when the lubricant is configured to burn out during the sintering of the powder metal composition.

[0016] In some forms, the powder metal composition may further contain ceramic powder additives to provide a metal matrix composite material upon sintering. The ceramic powder additive may be less than 15 volume percent of the powder metal, and the weight of the ceramic powder is not considered when calculating the weight percentage of the alloying elements. The ceramic powder additive has a specific surface area of ​​2.0 m². 2 It may also be aluminum nitride with a particle size distribution of 0.4-1.4 μm at D10%, 6-10 μm at D50%, and 17-35 μm at D90%. The specific surface area of ​​aluminum nitride is 1.8-3.8 m². 2 At a density of 10% / g, the particle size distribution is 0.2-0.6 μm for D10%, 1-3 μm for D50%, and 5-10 μm for D90%. Aluminum nitride (AlN) has a hexagonal crystal structure and is single-phase. In some forms, the ceramic additive is silicon carbide (SiC). Beta-silicon carbide is a synthetic SiC with a diamond-like cubic structure and possesses excellent physical and chemical properties. The Mohs hardness of β-SiC is second only to diamond at 10 on the Mohs hardness scale. In addition to its high hardness, β-SiC is characterized by its chemical stability, low thermal conductivity, and low coefficient of thermal expansion. In one embodiment, the amount of ceramic powder added to the powder metal composition is 2 volume% β-SiC relative to the total volume of the powder metal composition, with an upper limit of 10 volume%.

[0017] In some forms, the flow rate of the powder metal composition is in the range of 2.0 to 3.0 g / s. This flow rate may indicate the powder's form in ways not shown by other parameters of the powder metal.

[0018] According to another aspect, a green compact can be formed (for example, by compaction) from any of the powder metal compositions described above and herein. Similarly, a sintered powder metal part can be formed from such a green compact (for example, by sintering). The sintered density of the sintered powder metal part can exceed 95% of the theoretical density. Further, the sintered powder metal part that has been sintered and subjected to T6 treatment including solution treatment, water quenching, aging treatment, and air cooling may have a Young's modulus of 61 GPa to 77 GPa, a yield strength of 324 MPa to 344 MPa, and an ultimate tensile strength (UTS) of 324 MPa to 379 MPa.

[0019] These and other advantages of the present invention will be apparent from the detailed description and the drawings. The following is merely a description of several preferred embodiments of the present invention. To evaluate the full scope of the present invention, reference should be made to the claims, because these preferred embodiments are not intended to be the only embodiments within the scope of the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] [Figure 1A-1B] Figures 1A and 1B are scanning electron microscope (SEM) images of various powders used in the production of 6013 powder metal variants. Figures 1A and 1B are SEM images of the base aluminum powder used in the 6013 powder metal variant. Figure 1A is an image of pre-alloyed Al-0.6Mn powder metal, and Figure 1B is an image of pure aluminum powder. [Figure 1C-1D] Figures 1C and 1D are scanning electron microscope (SEM) images of various powders used in the production of 6013 powder metal variants. Figures 1C and 1D are SEM images of alloy additives, including elemental Mg powder metal in Figure 1C and Al-12Si master alloy powder metal in Figure 1D. [Figure 1E-1F]Figures 1E and 1F are scanning electron microscope (SEM) images of various powders used in the production of the 6013 powder metal variant. Figures 1E and 1F are SEM images of alloy additives, including elemental tin powder in Figure 1E and Al-50Cu master alloy powder metal in Figure 1F. [Figure 2A-2B] Figures 2A and 2B are SEM images of the sintered microstructures of PM6013-Mn in Figure 2A and PM6013-Mn-Sn in Figure 2B. Specific powder metal formulations in both the compositions and powder blends designated under the names PM6013-Mn and PM6013-Mn-Sn are provided in the detailed description below. [Figure 2C-2D] Figures 2C and 2D are SEM images of the sintered microstructures of PM6013 in Figure 2C and PM6013-Sn in Figure 2D. Specific powder metal formulations in both the compositions and powder blends designated under the names PM6013 and PM6013-Sn are provided in the detailed description below. [Figure 3A-3B] Figures 3A and 3B are SEM images of the sintered and swaged microstructures. Figures 3A and 3B are SEM images of the sintered and swaged microstructures, where Figure 3A is the SEM image of powder metal 6013 and Al-0.6Mn+0.5 wt% Sn powder metal (i.e., PM6013-Mn-Sn) in the as-sintered state, and Figure 3B is the SEM image thereof in the swaged state. [Figure 3C-3D] Figures 3C and 3D are SEM images of the sintered and swaged microstructures. Figures 3C and 3D are SEM images in the swaged state, where Figure 3C is the SEM image of powder metal 6013 using Al-0.6Mn+0 wt% Sn powder metal (i.e., PM6013-Mn), and Figure 3D is the SEM image of powder metal 6013 using Al-0.6Mn+0.5 wt% Sn powder metal (i.e., PM6013-Mn-Sn). [Figure 3E-3F]Figures 3E and 3F are SEM images of sintered and swaged microstructures. Figures 3E and 3F are SEM images of the swaged state, with Figure 3E being an SEM image of powder metal 6013 using pure Al + 0 wt% Sn powder metal (i.e., PM6013-Sn), and Figure 3F being an SEM image of powder metal 6013 using pure Al + 0.5 wt% Sn powder metal (i.e., PM6013-Sn). [Figure 4A-4B] Figures 4A and 4B show differential scanning calorimetry (DSC) heating traces obtained from 6013 powder metal variants, with Figure 4A showing the DSC heating trace of PM6013-Mn and Figure 4B showing the DSC heating trace of PM6013-Mn-Sn. [Figure 4C-4D] Figures 4C and 4D show differential scanning calorimetry (DSC) heating traces obtained from 6013 powder metal variants, with Figure 4C showing the DSC heating trace of PM6013 and Figure 4D showing the DSC heating trace of PM6013-Sn. [Figure 5A-5B] Figures 5A and 5B show the T6 aging data for variants of 6013 powder metal. The samples were sintered, hot swaged, then solution treated at 540°C in Figure 5A and 560°C in Figure 5B, followed by quenching in water and aging at 190°C. [Figure 5C] Figure 5C shows the T6 aging data for a variant of 6013 powder metal. The sample was sintered, hot swaged, then solution treated at 580°C (Figure 5C), followed by quenching in water and aging at 190°C. [Figure 6A-6B] Figures 6A and 6B show SEM images of the microstructure of PM6013 variants processed by the sintering-swaging-T6 sequence, respectively, with Figure 6A containing PM6013-Mn and Figure 6B containing PM6013-Mn-Sn. [Figure 6C-6D] Figures 6C and 6D show SEM images of the microstructure of PM6013 variants processed by the sintering-swaging-T6 sequence, respectively, with PM6013 in Figure 6C and PM6013-Sn in Figure 6D. [Figures 7A-7B]Figures 7A and 7B show the T8 aging data for powder metal 6013 variants obtained by sintering, hot-swaging, solution-thermalizing at 560°C, rapidly cooling with water, cold-working, and then aging at 190°C for a specified time. Figure 7A shows the T8 aging data for PM6013-Mn, and Figure 7B shows the T8 aging data for PM6013-Mn-Sn. [Figure 7C-7D] Figures 7C and 7D show the T8 aging data for powder metal 6013 variants obtained by sintering, hot-swaging, solution-firing at 560°C, quenching with water, cold-working, and then aging at 190°C for a specified time. Figure 7C shows the T8 aging data for PM6013, and Figure 7D shows the T8 aging data for PM6013-Sn. [Figure 8A-8B] Figures 8A and 8B show the microstructures of PM6013 variants processed by the sintering-swaging-T8 sequence, including PM6013-Mn in Figure 8A and PM6013-Mn-Sn in Figure 8B. [Figure 8C-8D] Figures 8C and 8D show the microstructures of PM6013 variants processed by a sintering-swaging-T8 sequence, including PM6013 in Figure 8C and PM6013-Sn in Figure 8D. [Figure 9A-9B] Figures 9A and 9B are graphs showing the tested mechanical properties of PM6013 variants across various conditions and alloys. Figure 9A shows the Young's modulus value ("E value"), and Figure 9B shows the elongation at fracture value. [Figure 9C-9D] Figures 9C and 9D are graphs showing the tested mechanical properties of PM6013 variants across various conditions and alloys. Figure 9C shows the 0.2% offset yield value, and Figure 9D shows the ultimate tensile strength (UTS). [Modes for carrying out the invention]

[0021] The powder metal compositions disclosed herein are comparable to those of 6013 aluminum alloy. Exemplary powder metal compositions and several variations thereof are disclosed below.

[0022] Four alloys were considered as powder metal counterparts to forged 6013 aluminum alloy. All of these had the same concentrations of magnesium, silicon, and copper. The alloy variations were prepared with or without pre-alloyed manganese and mixed tin. Manganese, used in forged 6031, was found in two of the four variations. Two manganese-free variations were also prepared because pre-alloying aluminum often increases the yield strength of the powder metal and can complicate the mold's compression behavior. For both the manganese-containing and manganese-free formulations, the addition of tin was also considered; one formulation was tin-free, while the other contained a trace amount of 0.5 wt% tin. Tin was considered because it helps catalyze the densification reaction of the powder metal alloy.

[0023] These four variant compositions are designated PM6013-Mn, PM6013-Mn-Sn, PM6013, and PM6013-Sn. The composition of each system is shown in Table 1, and all percentages represent the weight percentage of the total weight of the powder metal (excluding lubricant). [Table 1]

[0024] PM6013-Mn and PM6013-Mn-Sn compositions are Al-0.6Mn powder metal (0.6 wt% manganese is pre-alloyed with aluminum, and the remainder of the Al-0.6Mn powder (approximately 99.4 wt%) is aluminum) [D 50 =103μm], Al-12Si powder metal (12 wt% Si master alloy powder with the remainder being aluminum) [D 50 =33μm], Al-50Cu (50 wt% Cu master alloy powder with the remainder being aluminum) [D 50 =31μm] and individual mixed elemental powder metal [D 50 =31μm] and in the case of PM6013-Mn-Sn formulation, tin [D 50 It was formed from a mixture of [D = 4 μm]. The PM6013 and PM6013-Sn compositions are pure aluminum powder metal [D50 =116μm] with Al-12Si powder metal [D 50 =33μm], Al-50Cu powder metal [D 50 =31μm], and magnesium [D 50 =31μm] of separate mixed elemental powder metal additives (in the case of PM6013-Sn formulation, tin [D 50 =4μm]) were mixed to produce. All powders were manufactured by Kymera International (Raleigh, North Carolina), while the elemental magnesium powder was manufactured by Tangshan Weihao Magnesium Powder Company Ltd. (Qian'an, Hebei Province, China) via an inert gas atomization method. In all formulations, the various powder metal components are combined in ratios and proportions to achieve the target composition, and the exact powder amounts are not shown here, but given the powder metal "component" list for each formulation or variant, it is easy to back-calculate and find the exact proportions of the combined powder metals in each case.

[0025] Referring to Figures 1A to 1F, various powder metals mixed to prepare these alloy compositions are shown under a scanning electron microscope. Figure 1A shows the powder metal Al-0.6Mn, Figure 1B shows pure aluminum, Figure 1C shows elemental magnesium, Figure 1D shows Al-12Si, Figure 1E shows elemental Sn, and Figure 1F shows Al-50Cu (50 wt% Cu, the balance being aluminum).

[0026] For each powder metal composition, 1.5 wt% of LicoWax® C (available from Clariant Corporation in Louisville, Kentucky) was added to all mixtures to facilitate compression. LicoWax® C is a lubricant / wax that helps bind the compressed green parts together by holding the powder particles together, and further helps remove the green parts when removing them from the tool and die set after compression. The lubricant typically burns out during the sintering process in the preheating zone. Therefore, this 1.5 wt% is based on the powder metal component itself being 100 wt%, so the alloy percentage above should be understood as 100% of the powder metal, and the powder metal component and lubricant together actually amount to 101.5 wt%.

[0027] Furthermore, it is envisioned that these 6013 powder metal variants can be used to provide up to 15 volume percent of ceramic additives to create metal matrix composites that result in improved wear resistance and strength. Aluminum nitride (AlN) is the primary additive being considered for the 6013 powder metal variants, but silicon carbide (SiC) is another ceramic additive being considered as a viable option.

[0028] Regarding aluminum nitride (AlN) MMC additives, these aluminum nitride additives are considered to be, for example, grade AT aluminum nitride (aggregated powder with a broader particle size distribution) or grade BT aluminum nitride (relatively fine particle size, non-aggregated powder). Both grades can be used in the disclosed powder metal formulations, depending on the processing and properties.

[0029] Both AT-grade and BT-grade aluminum nitride have a hexagonal crystal structure and are single-phase. For the chemical characterization of these aluminum nitride additives, the mass fractions for both AT-grade and BT-grade are a minimum of 32.0% N, a maximum of 0.15% C, and a maximum of 0.05% Fe. However, the maximum oxygen content for AT-grade is 1.3%, while that for BT-grade is 1.5%. The specific surface area of ​​AT-grade is 2.0 m².2 Although the value is less than / g, the specific surface area of ​​BT grade is 1.8 to 3.8 m². 2 The particle size distribution is / g. The particle size distributions for two different grades are shown in Table 2 below. [Table 2]

[0030] Aluminum nitride, as an MMC additive, improves the wear resistance, ductility, and thermal conductivity of powder metal formulations. Compared to conventional MMC additives such as Al2O3 and SiC, tool wear is minimized.

[0031] In some forms, the ceramic additive can be silicon carbide (SiC). Beta-silicon carbide is a synthetic SiC with a diamond-like cubic structure and possesses excellent physical and chemical properties. The Mohs hardness of β-SiC is second only to diamond at 10 on the Mohs hardness scale. In addition to its high hardness, β-SiC is characterized by excellent chemical stability, high thermal conductivity, and a low coefficient of thermal expansion. In one embodiment, the ceramic powder additive in the powder metal composition is 2 volume% of β-SiC relative to the total volume of the powder metal composition, with an upper limit of 10 volume%.

[0032] When ceramic additives are used, the powdered metal, aluminum nitride or other ceramic additives, and lubricants are preferably mixed in a high-strength mixer during powder preparation to ensure that various particles, especially fine particles, are uniformly dispersed throughout the powdered metal composition mixture and separation is avoided.

[0033] The following methods were used for the alloy preparation and manufacturing of the powder metal samples investigated.

[0034] First, the starting powders were mixed in appropriate proportions using a Turbula shaker mixer. Alloy additives were sequentially added to the required base aluminum powder, with a 30-minute mixing time between each addition. The apparent density was evaluated for each mixture using an Arnold meter according to MPIF standard 48, and the flow characteristics were measured by passing 25 g of each powder mixture through a Kearney apparatus, yielding the values ​​in Table 3 below. [Table 3]

[0035] The manganese-containing alloys exhibited a higher apparent density and lower flow rate compared to those prepared using pure aluminum as the base powder. Both of these reactions may be related to the morphology of the base aluminum powder. The powder pre-alloyed with manganese (Figure 1A) had a spherical morphology, while the unalloyed base powder (Figure 1B) had an irregular shape. Irregularly shaped particles result in greater interparticle friction. Higher interparticle friction leads to greater separation between particles, resulting in fewer particles per unit volume and a lower apparent density. Based on this principle, the flow rates of PM6013 and PM6013-Sn should be slower than those of the manganese-containing alloys, but in reality, they are slightly faster. This may be because the particle size of the pure aluminum base powder is slightly coarser, allowing the particles to flow more efficiently.

[0036] Although the addition of tin did not have a statistically significant effect on the flow rate, it was found to increase the apparent density. Since tin is a relatively heavy element (118.7 g / mol), even a small amount can significantly increase the density of the lightweight aluminum alloy. For example, as shown in Table 4 below, the addition of 0.5 wt% tin increased the calculated theoretical density by 0.09 g / cc (approximately 3.3%). A similar increase was observed in the apparent density, suggesting that the results are mainly a direct reflection of the addition of heavy elements.

[0037] Once the powder metal was prepared, the samples were molded at 220 MPa using an Instron 5594-200HVL test frame, and the target green density of the green compact was 2.50 g / cc. Three different sample shapes were fabricated: a transverse breaking strength (TRS) sample (nominal 31.7 mm × 12.7 mm × 9.7 mm), a Charpy sample (nominal 75 mm × 10 mm × 10 mm), and a larger rectangular sample (nominal 20 mm × 92 mm × 10 mm). Green density was determined using a "wet" approach according to MPIF standard 42. Green strength was determined using the three-point bending method outlined in MPIF standard 15. Both were completed using TRS bars.

[0038] The compression responses of various variations of 6013 powder metal are shown in Table 4 below. For each formulation, the theoretical density of each composition is first shown, followed by the measured Green's intensity and Green's density (percentage of theoretical density). [Table 4]

[0039] The addition of tin did not have a statistically significant effect on these properties of green compact, but a significant difference was observed in systems using pre-alloyed manganese. PM6013 and PM6013-Sn showed approximately four times greater green strength compared to their manganese-containing counterparts. This difference, as well as fluidity and apparent density, is thought to be due to the morphology of the base powder particles. Particle shape can be a factor influencing the green strength of compact; if the base powder pre-alloyed with manganese is spherical, surface contact between particles is limited, potentially resulting in lower green strength. In contrast, the irregular shape of unalloyed aluminum base powder may increase the opportunities for mechanical entanglement of particles during molding, potentially leading to higher green strength. Pre-alloying the base powder with manganese further enhances this effect by strengthening spherical particles, increasing resistance to the plastic deformation necessary for entanglement.

[0040] Next, these samples were sintered in a 3-zone Lindberg tube furnace while flowing high-purity (99.999%) nitrogen gas. Before heating, multiple evacuations (10 -2 The furnace atmosphere was adjusted by a torr and backfill sequence, and a static gas flow rate of 9.4 liters / min was maintained throughout the sintering cycle. The thermal profile of the sintering furnace was maintained by holding it at 420°C for 20 minutes for de-slippage and then at 630°C for 30 minutes for sintering when sintering TRS and Charpy samples. Larger rectangular rods were held at 630°C for 50 minutes to ensure complete sintering. After the sintering time had elapsed, the samples were gas-quenched by sliding them into the water jacket end of the tube furnace and cooled to ambient temperature under a nitrogen atmosphere. TRS samples were used to monitor the general sintering behavior of the alloy. Data on sintering density, dimensional change, and mass change caused by sintering were compiled. To quantify dimensional change, measurements of width, length, overall length (OAL), or thickness of each sample before and after sintering were obtained. Sintering density was evaluated using the oil-penetration Archimedes method according to MPIF standard 42. Density measurements were reported as a percentage of the theoretical complete density calculated for the alloy using a method specified by the Aluminum Society. This data is reported in Table 5 below. [Table 5]

[0041] All alloys exhibited a mass loss of approximately 1.5 wt% corresponding to the boiling and evaporation of the lubricant during sintering, although there was considerable variability in sinter density and compact warpage. Manganese-containing alloy variants (PM6013-Mn and PM6013-Mn-Sn) did not respond favorably to sintering. Here, the sinter density was inferior to the Green density, and the compact actually experienced net expansion at all dimensions. Manganese-free alloys (PM6013 and PM6013-Sn) sintered to a much higher degree. The sinter density of these manganese-free material variants exceeded 96%, a measurably improved result compared to the density of the initial Green compact. This improvement was consistent with dimensional changes, as shrinkage was observed in all directions.

[0042] The addition of tin did not improve the sintering responsiveness of PM6013-Mn, as it resulted in both expansion and a decrease in sinter density. However, when comparing PM6013 and PM6013-Sn, the sintering responsiveness of PM6013 was further improved by the addition of tin. This may be related to the behavior of tin during liquid-phase sintering. Because tin has a lower melting point than other alloy additives, it usually forms part of the liquid phase that densifies the compressed material. Therefore, it was expected that the addition of tin to PM6013-Mn-Sn and PM6013-Sn would result in a slightly higher proportion of liquid present during the liquid-phase sintering of these alloys compared to PM6013-Mn and PM6013. A high liquid fraction in liquid-phase sintering leads to rapid densification, but dimensional control can become difficult as densification progresses. However, since only a small amount of tin was added, this does not fully explain the observed effect. Aluminum powder always reacts with oxygen to form a thin alumina layer (Al2O3) on the surface of the powder. The increased apparent density of the manganese-containing alloy indicates that the particles are more densely packed, resulting in a higher amount of oxide per unit volume compared to the manganese-free alloy. The inability of tin to wet alumina is thought to have influenced the difference in the sintering reactions of the two tin-containing alloys.

[0043] Interestingly, the alloys that achieved higher Green densities, PM6013-Mn and PM6013-Mn-Sn, also had lower sintering densities and, consequently, lower densities during sintering. Theoretically, a compact with good sintering should measure a higher Green density, since density is generally a function of Green density. However, this was not the case here, which was an unexpected and surprising result. It is useful to examine the net changes in apparent density and Green density for PM6013-Mn and PM6013-Mn-Sn. PM6013-Mn and PM6013-Mn-Sn show net changes in apparent density and Green density of 1.2 g / cc and 1.1 g / cc, respectively. In contrast, PM6013 and PM6013-Sn show slightly higher net changes of 1.3 g / cc and 1.4 g / cc, respectively. This indicates that compression of PM6013-Mn and PM6013-Mn-Sn results in less material migration than compression of manganese-free alloys. This suggests that the particles were not mechanically bonded effectively, which is also evident in the relatively low Green strength of these two alloys. Material migration also serves to break down the oxide film on the powder and provide space for mechanical bonding between metals. Reduced material migration means fewer metal-to-metal contact sites are established between particles, which can inhibit sintering. Increased interparticle contact in PM6013 and PM6013-Sn allows these alloys to sinter more efficiently.

[0044] The differences between these two sintering responses were particularly pronounced in terms of microstructure, as shown in Figures 2A-2D.

[0045] Figures 2A-2D show the post-sintering microstructure observed with a scanning electron microscope. Figure 2A corresponds to PM6013-Mn, Figure 2B to PM6013-Mn-Sn, Figure 2C to PM6013, and Figure 2D to PM6013-Sn. All of these samples are shown in their post-sintering state without swaging. For microstructure evaluation, the samples were hot-mounted in conductive epoxy and then polished using a Struers Tegramin semi-automatic polishing machine. Standard polishing media such as silicon carbide paper, diamond paste, and colloidal silica were used. Optical microscopy was performed using a Zeiss Axiotech upright microscope and a Keyence VK-X1000 laser confocal microscope (optical mode). Electron microscopy was performed using a Hitachi S-4700 cold field emission scanning electron microscope (SEM) operating at an acceleration voltage of 20kV and a beam current of 20mA. Energy-dispersive spectroscopy (EDS) is performed using the Oxford Instruments X-Max 80mm 2 The procedure was performed using an EDS detector.

[0046] The alloys PM6013-Mn (Figure 2A) and PM6013-Mn-Sn (Figure 2B) were found to have poor sintering quality. Evidence of the starting powder morphology remained, and the microstructure showed numerous irregular, continuous pores (black features). These factors indicate that sintering bonding was achieved only in the initial stages.

[0047] In contrast, samples produced without manganese (PM6013 (Figure 2C) and PM6013-Sn (Figure 2D)) were sintered to a much higher quality. Raw powder particles were no longer visible, and the remaining few pores were round and discontinuous.

[0048] Next, sintered rods of each alloy were processed by hot swaging. The sintered rectangular samples were processed into cylindrical shapes (18 mm in diameter, 90 mm in length), preheated to 485°C, and then hot-swaged in a laboratory-scale apparatus. In this process, the samples were passed through small dies repeatedly until the final diameter was 12.7 mm, and with an extrusion ratio of 2:1, the area was reduced by approximately 50%. The samples were reheated at 485°C for 5 minutes between each pass.

[0049] Macroscopically, all alloys reacted well, and considering the various microstructures shown in Figures 3B-3F after swaging, no visible defects were observed in the finished products after swaging. Microstructurally, comparing the microstructure before swaging (Figures 2A, 2B, 3A, etc.) with the microstructure after swaging (Figure 3B, etc.), the effect of swaging was immediately apparent in the manganese-containing alloys. Swaging closed most of the pores remaining in the material after sintering. The remaining pores became smaller and less continuous. For clarity, Figure 3A shows only the PM6013-Mn-Sn sample after sintering, while Figure 3B shows a comparison of the PM6013-Mn-Sn sample after sintering and after swaging. Figures 3C to 3F show images of the sintered and swaged microstructures of PM6013-Mn (Figure 3C), PM6013-Mn-Sn (Figure 3D), PM6013 (Figure 3E), and PM6013-Sn (Figure 3F).

[0050] Figures 3B-3F above show that swaging was performed on all powder metal 6013 variants. Qualitative observations revealed that all alloy formulations swaged well, with no external cracks or fissures. Furthermore, swaging homogenized the microstructure. All microstructures were dominated by white α-aluminum particles, and there was no evidence of secondary grain boundary phase coarsening as a result of the heat applied during hot swaging. A small amount of residual pores remained in all microstructures, consistent with the measured swaging density. The residual pores were observed to be primarily grain boundary properties.

[0051] Similar to industrial extrusion processes, when viewed longitudinally, the particles are elongated in the direction of swaging. Furthermore, as expected from hot deformation processes, evidence of metal flow can be seen when examining the edges of the microstructure.

[0052] To further characterize the differences between "immediately after sintering" and "immediately after swaging" samples, the density of each formulation immediately after swaging was collected and compared to the density immediately after sintering (the average sintering density for each formulation is also shown in Table 5 above). These are shown in Table 6 below, again expressed as a percentage of the theoretical density for a particular formulation. [Table 6]

[0053] Table 6 above shows that the density of all swaged powder metal alloy compositions, including the sample containing Al-0.6Mn which did not show densification during sintering, improved with swaging. The swaged sample made from Al-0.6Mn powder metal (in contrast to the combination of pure aluminum and elemental magnesium) was slightly longer due to the closure of more pores. No significant differences were observed in the swaging response of the alloys among the four types of powder metals that were swaged. The average swaged density for all was over 99% of the theoretical density, and the two samples made from pure aluminum were slightly closer to the theoretical density than the two samples made from Al-0.6Mn, which is thought to be partly due to their higher initial density before swaging.

[0054] Because the sintering densities of PM6013 and PM6013-Sn were significantly higher, the difference in microstructure before and after swaging was not very pronounced. However, the amount of residual pores in each alloy decreased to a measurable level, and the density of all materials after swaging exceeded 99% of the theoretical value. Specifically, the swaged densities of PM6013 and PM6013-Sn were 99.5% and 99.4% of the theoretical value, respectively. In contrast, the densities of PM6013-Mn and PM6013-Mn-Sn were slightly lower, at 99.1%. The slight improvement in the measured values ​​for PM6013 and PM6013-Sn is due to the high sintering density (see Table 5) and the significantly smaller amount of residual pores that needed to be removed at the same time.

[0055] Since forged 6013 is a heat-treatable alloy, the effects of T6 and T8 processes on PM6013 variants were also investigated. Both begin with a solution treatment step, primarily aimed at dissolving precipitate-forming elements into a solid solution. Establishing the appropriate temperature for this step is crucial and is frequently investigated using differential scanning calorimeter (DSC). DSC tests provide data on the melting behavior of the alloy, thereby guiding the study of appropriate solution treatment temperature ranges.

[0056] Therefore, the melting behavior of the swaged specimens was evaluated using a Netzsch 404 F1 differential scanning calorimeter. Temperature and sensitivity calibration was performed before testing. All tests were conducted in a controlled atmosphere while flowing high-purity nitrogen gas at 50 ml / min. Circular samples were machined from swaged rods (4 mm in diameter, 2 mm thick). The samples were heated to 700°C at a rate of 20°C / min and then cooled to ambient temperature at the same rate.

[0057] Referring to Figures 4A–4D, differential scanning calorimetry data in the form of heat flux traces of samples made from 6013 powder metal variants are provided over a range of 100°C–700°C under a controlled atmosphere. As previously mentioned, Figure 4A is PM6013-Mn, Figure 4B is PM6013-Mn-Sn, Figure 4C is PM6013, and Figure 4D is PM6013-Sn.

[0058] The "A" and "B" indicators in these figures indicate melting events at the specific temperatures shown. Two melting events are observed for PM6013-Mn-Sn and PM6013-Sn, while only one melting event is observed for PM6013-Mn and PM6013. All plots show the primary melting event, labeled "A". The peak size is relatively constant across the alloy and began at approximately 580°C. This event is thought to correspond to the overall melting of the alloy as the temperature increased through the semi-solid state. The thermal traces of the tin-containing alloy (Figures 4B and 4D) include a smaller secondary event (peak B) occurring between approximately 540°C and 580°C. This is presumed to indicate the initial melting of the tin-containing phase. The thermal traces in Figures 4A and 4C also show small fluctuations around the same location as peak "B". This likely indicates that melting had begun in these alloys as well, but the significantly larger peak value "B" in the traces in Figures 4B and 4D suggests that the effect was amplified by tin.

[0059] The solution temperature itself needs to be higher than the sorbus temperature, but it is usually not high enough to cause partial melting. The typical solution temperature for forged 6013 is 570°C. This is lower than the bulk melting initiation temperature, but lies in the middle valley of event "B". Therefore, the same temperature cannot be arbitrarily applied to the powder metal system, as it could cause liquid formation and reduce the concentration of alloying elements dissolved in the solid solution. Thus, a series of solutions temperature experiments were needed both above and below peak B. For this purpose, solutions tests at 540°C, 560°C, and 580°C were selected.

[0060] Two heat treatment conditions, T6 and T8, were considered for the post-swaging treatment. Under T6 conditions, the swaged rods were solution-treated in air at 560°C for 2 hours (Lindberg box furnace), quenched in water, and then aged at 190°C (Heratherm mechanical convection oven). To achieve T8 conditions, the samples underwent the same solution / quenching treatment, but were then cold-worked to reduce the average thickness by 11%, and then aged at 190°C.

[0061] Furthermore, T6 aging curves were created using the solution temperature identified by DSC evaluation, shown in Figure 5A for a 540°C solution temperature, Figure 5B for a 560°C solution temperature, and Figure 5C for a 580°C solution temperature. All curves showed that hardness increased to its peak at approximately 5 hours of artificial aging. In all alloys, the lowest hardness measurements were consistently obtained at 580°C, suggesting a microstructure with little precipitate formation. This indicates that the solution temperature was too high. There was little distinction between the 540°C and 560°C aging curves. The 560°C aging curve showed less consistency between hardness measurements compared to the curve created at 540°C. However, when 560°C was used as the solution temperature, the highest hardness measurements were obtained across the entire alloy during the creation of the aging curve. For convenience and clarity, the peak hardness (T6 at a solution temperature of 560°C) in Figure 5B was 102 HRE for PM6013-Mn, 98 HRE for PM6013-Mn-Sn, 102 HRE for PM6013, and 100 HRE for PM6013-Sn.

[0062] These results indicate that the most effective T6 heat treatment cycle across all variations is a cycle of solution treatment at 560°C, followed by quenching in water and aging at 190°C for 5 hours. These heat treatment parameters were used for the remainder of the study.

[0063] SEM images of samples in the T6 state are shown in Figures 6A-6D. In all cases, a small proportion of residual pores was observed, as was the case for secondary grain boundary components. In PM6013-Mn (Figure 6A), the grain boundary structure was light gray, relatively coarse, and in some cases, fractured. The latter is thought to have occurred during hot swaging, as no cracks were observed in this structure in the micrograph immediately after sintering in Figure 2A. EDS analysis showed high concentrations of manganese (25 wt%) and silicon (10 wt%), mainly aluminum. A similar phase was observed in PM6013-Mn-Sn (Figure 6B), which also indicated fracture. Secondary grain boundary structures were also observed in the alloys. These were brighter than the Mn-containing structure (left image), and EDS confirmed that tin was concentrated. Since PM6013 did not contain manganese or tin, none of the aforementioned grain boundary features were observed in the microstructure of Figure 6C. Here, secondary features were finer and distributed somewhat more uniformly throughout the microstructure. EDS showed that it was mainly aluminum, with high and varying concentrations of silicon (4-7 wt%), magnesium (1-2 wt%), and copper (1-4 wt%). In Figure 6D of PM6013-Sn, a tandem of grain boundary features was again observed. One was similar to that observed in PM6013, but this time containing a small amount of tin (approximately 1 wt%). The second was brighter, with high concentrations of tin (47 wt%) and magnesium (22 wt%), with the remainder being aluminum. No evidence of cracking was found in any of the grain boundary features in PM6013 or PM-6013-Sn.

[0064] Subsequently, the evaluation of the T8 aging reaction was completed. Figures 7A–7D show hardness data as a function of aging time for samples of PM6013-Mn, PM6031-Mn-Sn, PM6013, and PM6013-Sn variants, respectively. These samples were subjected to sintering, hot swaging, solution treatment at 560°C, water quenching, cold working, and aging for a specified time at 190°C. All alloys were very similar in this respect, and their peak hardnesses were similar (70–76 HRB). In general, hardness steadily decreased with aging time beyond the initial period examined (1 hour). This behavior suggests that the peaks in the curves were likely missed during the aging experiments. However, since all curves showed a relatively gentle slope in the initial stages, the difference between the true peak values ​​and the values ​​suggested by the data was probably minimal. In this study, 1 hour was adopted as the aging time required to achieve the highest hardness with T8 treatment. Figures 5A-5C show that the T6-treated samples exhibited a maximum hardness value of 65-76 HRB (i.e., 98-101 HRE). Therefore, the maximum value recorded for the T8 sample is quite similar to the value achieved with the T6 treatment.

[0065] SEM images were acquired for all samples under T8 conditions and are shown in Figures 8A–8D. PM6013-Mn is shown in Figure 8A, PM6013-Mn-Sn in Figure 8B, PM6013 in Figure 8C, and PM6013-Sn in Figure 8D. In all cases, the microstructure of T8 is very similar to that of the corresponding T6 samples (Figures 6A–6D). The only difference is in the case of PM6013-Mn. In the case of PM6013-Mn, the cracks are no longer limited to the boundaries of the grain structure, but extend throughout the microstructure as sporadic cracks several hundred microns in length. This is due to the cold working stage of the T8 process.

[0066] With the heat treatment parameters established, the focus of the study shifted to evaluating the mechanical properties of each alloy system, T6 and T8 grade, including the effects of swaging. Mechanical testing included measurements of hardness, tensile properties, and bending fatigue performance. Hardness data were obtained using a Wilson Rockwell 2000 testing machine on the Rockwell Hardness E scale (HRE) and Rockwell Hardness B scale (HRB). Reported values ​​were obtained as the average of four measurements. Tensile properties were evaluated according to ASTM standard E8-M. Swaged rods and Charpy bars were machined to become threaded end tensile test specimens, which were then loaded until fracture on an Instron 5594-200HVL load frame equipped with a 50kN load cell and an Epsilon Model 3542 extensometer. The extensometer was attached to each sample until fracture. The reported tensile properties for the T6 and T8 samples are averages obtained from three and two test samples, respectively. Bending fatigue characteristics were evaluated according to MPIF standard 56 using the step method with a step size of 5 MPa under three-point loading conditions. All samples were rectangular (31.7 mm × 12.7 mm × 9.7 mm) and tested using an Instron 1332 servo-hydraulic frame with MTS642 bending fixtures maintaining a span of 24.7 mm between the two lower pins. The load was applied at 25 Hz (R=0.1) up to the runout limit of 10⁶ cycles. From the resulting data, residual stress values ​​of 10%, 50%, and 90% were calculated.

[0067] Tensile properties were obtained for T6 pressed and sintered (post-sintered), T6 swaged, and T8 swaged parts. This data is summarized in graphs in Figures 9A-9D, following the table and explanation below. Figures 9A-9D show a comparison of data for various measurement characteristics (Figure 9A: Young's modulus, Figure 9B: elongation at break, Figure 9C: offset yield, and Figure 9D: UTS) across various conditions and compositions.

[0068] The various tensile properties of 6013 powder metal were measured in samples that were treated with a sintering T6 sequence, then solution-treated at 560°C for 2 hours, quenched in water, aged at 190°C for 5 hours, and air-cooled. These tensile properties are listed in Table 7 below, including a forged 6013 aluminum alloy sample for comparison. [Table 7]

[0069] From the table above, it can be seen that pressed and sintered samples made from variations of 6013 powder metal (particularly PM6013-Sn) have mechanical properties that are very similar to or nearly equivalent to forged 6013 aluminum alloy samples. However, it can also be seen that as-sintered samples (without further swaging) made from Al-0.6Mn (i.e., PM6013-Mn and PM6013-Mn-Sn) have relatively lower mechanical performance. Thus, all powder metal systems performed inferiorly to their forged counterparts, but the difference was most pronounced in those containing pre-alloyed manganese. These materials had exceptionally low values ​​for all properties, directly due to the high level of residual porosity present in them (Table 5 above). In contrast, PM6013 and PM6013-Sn showed superior performance in terms of stiffness and yield strength, with these particular properties being within approximately 10% of typical forged values. The UTS of PM6013 was considerably lower than that of the forged alloy, but this was improved in PM6013-Sn. The average tensile ductility of the pressed and sintered samples was approximately 13 times lower than that of the typical forged alloy. This significant difference may be due to the presence of residual porosity in all powder metal systems, which is almost absent in the forged alloy. Overall, PM6013-Sn exhibited the most desirable T6 tensile properties, supporting the beneficial role of tin.

[0070] By adding a swaging step to the processing sequence, the performance difference between forged 6013 (Table 7) and all the powder metal variants (Table 8) below was significantly reduced. For ease of comparison, the post-sintering data from Table 7 is copied below and identified as "Press & Sinter". [Table 8]

[0071] In swaged parts, improvements in 0.2% offset yield strength and UTS were particularly significant for all powder metals, with these properties being substantially equivalent to those of forged parts. Improved ductility was also observed, although none of the powder metal systems achieved a net value matching the forging threshold.

[0072] On average, swaged T6 powder metal samples showed approximately nine times greater ductility compared to those treated with sintered T6 without swaging.

[0073] Hot swaging reduced the residual pore levels in all powder metal materials, but it could not completely eliminate them. While this effect likely underpinned the significant benefits achieved, it also meant that the powder metal systems could not maintain ductility comparable to forged 6013, as residual pores acted as crack initiation sites and limited net ductility. Hot swaging likely contributed to improved ductility by disrupting the semi-continuous oxide network, which is also normally present in sintered products. During sintering, the alumina shell on the surface of the raw aluminum powder reacts with magnesium to form spinel microcrystals (MgAl2O3). This brittle ceramic remains throughout the sintered product, reducing tensile ductility. Hot forging has been observed to disrupt the spinel network, thereby improving tensile ductility. It is reasonable to assume that the same mechanism is at work here. It is also noteworthy that the fractured grain boundary phases observed in Figures 6A and 6B did not significantly reduce ductility. Other tensile properties were relatively constant across all four alloys. Overall, PM6013-Sn was identified as a powder metal alloy that offers the best overall combination of properties, possessing superior ductility and yield strength, UTS, and stiffness comparable to forged products.

[0074] Table 9 below shows the data for PM6013 variants processed using the sintering-swaging-T8 sequence (treatment at a solution temperature of 560°C for 2 hours, followed by water cooling, sizing, and aging at 190°C). [Table 9]

[0075] These specific materials exhibited the highest yield strength and UTS among all sequences examined, with no significant trend observed depending on the presence or absence of manganese or tin. The higher values ​​were due to a slight decrease in tensile ductility compared to materials that underwent the sintering swage T6 process. This decrease may be partly attributable to the cold working stage of the T8 heat treatment, as the cold working stage increases the concentration of existing dislocations, leading to strain hardening and a resulting decrease in ductility. The properties and distribution of precipitates should have changed as a result of the T8 treatment, and were also influencing factors. In this sense, cold working may alter the rate and degree of hardening because precipitates preferentially nucleate on dislocations, increasing the concentration of precipitates within the microstructure. The additional strengthening resulting from this change may have been accompanied by a decrease in ductility. Overall, PM6013-Mn had the lowest ductility. This is likely due to a combination of the aforementioned mechanisms and cracks observed in the microstructure (Figure 8A).

[0076] Furthermore, it was found that alloys containing pure aluminum in the base aluminum powder have higher ductility than alloys in which aluminum is pre-alloyed to the base aluminum powder (Al-0.6Mn), alloys containing tin have higher ductility than alloys without tin, and alloys without tin have a higher UTS value compared to tin.

[0077] In summary, powder metal 6013 systems treated with a sintering-swaging-T6 / T8 sequence showed relatively good performance compared to forged 6013. In particular, PM6013-Sn exhibited properties closest to those achieved by forging and outperformed all other powder metal alloys in terms of tensile ductility, regardless of the treatment sequence employed. Therefore, the final stage of fatigue evaluation focused solely on this specific powder metal system.

[0078] Finally, Table 10 shows the fatigue performance data for PM6013-Sn for the three processing sequences examined. [Table 10]

[0079] Sintered T6 products were shown to have the lowest resistance to fatigue loading. Including a hot swaging step (i.e., sintered swaging T6) increased the median bending fatigue strength by 102 MPa (approximately 68%). This is significant because hot swaging addresses two factors known to negatively impact fatigue: residual pores and the present oxide network. Considering the former, fatigue generally increases exponentially with density, and even a slight decrease in the volume fraction of residual pores can have a significant impact by reducing the number of sites available for crack nucleation and growth. Therefore, although the density increase of PM6013-Sn due to swaging was relatively small (approximately 1%), the net effect on fatigue was considered to be decisively positive. Regarding the latter, as mentioned above, the breakdown of the oxide network by hot swaging contributed to improved fatigue resistance, as did the improvement in tensile ductility. Dispersing fine particles of the brittle spinel phase throughout the material reduces the crack nucleation sites, and further strengthening is achieved through a mechanism similar to the strengthening present in metal matrix composites.

[0080] Samples obtained using the sintered swage T8 process were also significantly improved compared to the sintered T6 material (an increase of approximately 43%) for the same reasons as described above. However, they were still inferior to the sintered swage T6 product (by approximately 15%). The decrease in ductility observed in the T8 samples in tensile properties is thought to have contributed to these results.

[0081] From the above description and disclosure, the following can be concluded: First, pre-alloying the base aluminum powder with manganese reduces compression and sintering behavior. Second, all 6013-based powder metal alloys responded well to hot swaging, achieving a density close to the theoretical density (over 99% of the theoretical value) with no visible defects. Third, adding hot swaging to the processing sequence significantly improved the yield strength, UTS, ductility, and fatigue performance of the T6 and T8 tempered materials. Finally, sintered swaged T6PM6013-Sn was the best system overall in terms of its reaction to powder metal processing and comparison of its mechanical properties with forged 6013-T6. While other variations are certainly usable, this processing route and configuration is the most promising for powder metal comparable to forged 6013.

[0082] It should be understood that various other modifications and changes can be made to preferred embodiments within the spirit and scope of the present invention. Therefore, the present invention should not be limited to the embodiments described. To see the full scope of the present invention, one should refer to the following claims.

Claims

1. A powder metal composition that provides a powder metal material comparable to a forged 6013 aluminum alloy after compression, sintering, and heat treatment, The aforementioned powder metal composition is Aluminum-based powder metal, Aluminum-silicon powder metal, Aluminum-copper powder metal, Elemental magnesium powder metal, It consists of, The aluminum-based powder metal is either pure aluminum that does not contain any effective alloying elements, or a powder metal containing pure aluminum and alloying elements in an amount of 2% by weight or less of the aluminum-based powder metal. The weight percentage of silicon in the powder metal composition is within the range of 0.6 to 1.0% by weight of the powder metal composition. The weight percentage of copper in the aforementioned powder metal composition is within the range of 0.7 to 1.1% by weight of the powder metal composition. The weight percentage of magnesium in the aforementioned powder metal composition is within the range of 0.8 to 1.2% by weight of the powder metal composition. The material further contains ceramic powder additives for providing a metal matrix composite during sintering, The ceramic powder additive is less than 15% by volume of the powder metal. The weight of the aforementioned ceramic powder additive is not taken into consideration when calculating the weight percentage of the alloying element. Powder metal composition.

2. The aluminum-based powder metal is pure aluminum that does not contain any effective alloying elements pre-alloyed in the aluminum-based powder metal. The powder metal composition according to claim 1.

3. A powder metal composition that provides a powder metal material comparable to a forged 6013 aluminum alloy after compression, sintering, and heat treatment, The aforementioned powder metal composition is Aluminum-based powder metal, Aluminum-silicon powder metal, Aluminum-copper powder metal, Elemental magnesium powder metal, Elemental tin powder metal, It consists of, The aluminum-based powder metal is pure aluminum that does not contain any effective alloying elements that have been pre-alloyed in the aluminum-based powder metal. The weight percentage of silicon in the powder metal composition is within the range of 0.6 to 1.0% by weight of the powder metal composition. The weight percentage of copper in the aforementioned powder metal composition is within the range of 0.7 to 1.1% by weight of the powder metal composition. The weight percentage of magnesium in the aforementioned powder metal composition is within the range of 0.8 to 1.2% by weight of the powder metal composition. The weight percentage of tin in the aforementioned powder metal composition is within the range of 0.2 to 1.0% by weight of the powder metal composition. The material further contains ceramic powder additives for providing a metal matrix composite during sintering, The ceramic powder additive is less than 15% by volume of the powder metal. The weight of the aforementioned ceramic powder additive is not taken into consideration when calculating the weight percentage of the alloying element. Powder metal composition.

4. The weight percentage of silicon in the powder metal composition is more narrowly within the range of 0.7 to 0.9% by weight of the powder metal composition. The weight percentage of copper in the powder metal composition is more narrowly within the range of 0.8 to 1.0% by weight of the powder metal composition. The weight percentage of magnesium in the powder metal composition is more narrowly within the range of 0.9 to 1.1% by weight of the powder metal composition. The weight percentage of tin in the aforementioned powder metal composition is more narrowly within the range of 0.4 to 0.6% by weight of the powder metal composition. The remainder of the aforementioned powder metal composition is aluminum with only trace amounts of other alloying elements added that have no effect. The powder metal composition according to claim 3.

5. The weight percentage of silicon in the aforementioned powder metal composition is 0.8% by weight of the powder metal composition. The weight percentage of copper in the aforementioned powder metal composition is 0.9% by weight of the powder metal composition. The weight percentage of magnesium in the aforementioned powder metal composition is 1.0% by weight of the powder metal composition. The weight percentage of tin in the aforementioned powder metal composition is 0.5% by weight of the powder metal composition. The powder metal composition according to claim 4.

6. The aluminum-based powder metal is an aluminum powder metal that has been pre-alloyed with manganese such that the weight percentage of manganese in the powder metal composition is within the range of 0.2 to 1.2% by weight of the powder metal composition. The powder metal composition according to claim 1.

7. The weight percentage of manganese in the powder metal composition is more narrowly within the range of 0.4 to 0.6% by weight of the powder metal composition. The powder metal composition according to claim 6.

8. The weight percentage of manganese in the powder metal composition is 0.5% by weight of the powder metal composition. The powder metal composition according to claim 7.

9. A powder metal composition that provides a powder metal material comparable to a forged 6013 aluminum alloy after compression, sintering, and heat treatment, The aforementioned powder metal composition is Aluminum-based powder metal, Aluminum-silicon powder metal, Aluminum-copper powder metal, Elemental magnesium powder metal, Elemental tin powder metal, It consists of, The aluminum-based powder metal is an aluminum powder metal that has been pre-alloyed with manganese such that the weight percentage of manganese in the powder metal composition is within the range of 0.2 to 1.2% by weight of the powder metal composition. The weight percentage of silicon in the powder metal composition is within the range of 0.6 to 1.0% by weight of the powder metal composition. The weight percentage of copper in the aforementioned powder metal composition is within the range of 0.7 to 1.1% by weight of the powder metal composition. The weight percentage of magnesium in the aforementioned powder metal composition is within the range of 0.8 to 1.2% by weight of the powder metal composition. The weight percentage of tin in the aforementioned powder metal composition is within the range of 0.2 to 1.0% by weight of the powder metal composition. The material further contains ceramic powder additives for providing a metal matrix composite during sintering, The ceramic powder additive is less than 15% by volume of the powder metal. The weight of the aforementioned ceramic powder additive is not taken into consideration when calculating the weight percentage of the alloying element. Powder metal composition.

10. A powder metal composition that provides a powder metal material comparable to a forged 6013 aluminum alloy after compression, sintering, and heat treatment, The aforementioned powder metal composition is Aluminum-based powder metal, Aluminum-silicon powder metal, Aluminum-copper powder metal, Elemental magnesium powder metal, Elemental tin powder metal, It consists of, The aluminum-based powder metal is either pure aluminum that does not contain any effective alloying elements, or a powder metal containing pure aluminum and alloying elements in an amount of 2% by weight or less of the aluminum-based powder metal. The weight percentage of silicon in the powder metal composition is within the range of 0.6 to 1.0% by weight of the powder metal composition. The weight percentage of copper in the aforementioned powder metal composition is within the range of 0.7 to 1.1% by weight of the powder metal composition. The weight percentage of magnesium in the aforementioned powder metal composition is within the range of 0.8 to 1.2% by weight of the powder metal composition. The weight percentage of tin in the aforementioned powder metal composition is within the range of 0.2 to 1.0% by weight of the powder metal composition. The material further contains ceramic powder additives for providing a metal matrix composite during sintering, The ceramic powder additive is less than 15% by volume of the powder metal. The weight of the aforementioned ceramic powder additive is not taken into consideration when calculating the weight percentage of the alloying element. Powder metal composition.

11. The aluminum-silicon powder metal is Al-12Si master alloy powder metal. The aluminum-copper powder metal is Al-50Cu master alloy powder metal. The powder metal composition according to claim 1.

12. The aforementioned powder metal composition further comprises a lubricant, Since the lubricant is configured to burn during the sintering of the powder metal composition, the weight percentage of the alloying element excludes the weight of the lubricant. The powder metal composition according to claim 1.

13. The aforementioned ceramic powder additive has a specific surface area of ​​2.0 m². 2 The aluminum nitride has a particle size distribution of 0.4–1.4 μm at D10%, 6–10 μm at D50%, and 17–35 μm at D90%. The powder metal composition according to claim 1.

14. The aluminum nitride (AlN) has a specific surface area of ​​1.8 to 3.8 m². 2 The particle size distribution is 0.2–0.6 μm at D10%, 1–3 μm at D50%, and 5–10 μm at D90%. The powder metal composition according to claim 13.

15. The aluminum nitride (AlN) has a hexagonal crystal structure and is single-phase. The powder metal composition according to claim 13.

16. The ceramic powder additive is silicon carbide. The powder metal composition according to claim 1.

17. The silicon carbide is β-silicon carbide, is in the range of 2% to 10% by volume of the powder metal, and the weight of the ceramic powder additive is not considered when calculating the weight percentage of the alloying element. The powder metal composition according to claim 16.

18. The flow rate of the aforementioned powder metal composition is 2.0 to 3.0 g / second. The powder metal composition according to claim 1.

19. A green compact formed from the powder metal composition described in claim 1.

20. A sintered powder metal part formed from the green compact described in claim 19.

21. The sintered powder metal part according to claim 20, wherein the sintering density of the sintered powder metal part exceeds 95% of the theoretical density.

22. Sintered powder metal parts that have undergone T6 treatment (sintering, solution treatment, water quenching, aging treatment, and air cooling) have a Young's modulus of 61 GPa to 77 GPa, a yield strength of 324 MPa to 344 MPa, and an ultimate tensile strength (UTS) of 324 MPa to 379 MPa. The sintered powder metal part according to claim 20.

Citation Information

Patent Citations

  • Aluminum alloy powder and manufacturing method of aluminum alloy object

    CN108070752A

  • Aluminium-alloy powder, sintered aluminium-alloy, and method for producing the sintered aluminum-alloy

    EP0436952A1

  • Manufacture of superplasticity silicon nitride whisker reinforced aluminum alloy composite

    JP1991107433A

  • Aluminum-aluminum nitride composite material and its production

    JP1996003601A

  • Mixture of aluminum alloy powder metals

    JP2012505312A